1983
DOI: 10.1161/01.hyp.5.2.185
|View full text |Cite
|
Sign up to set email alerts
|

Hypoalgesia in genetically hypertensive rats (SHR) is absent in rats with experimental hypertension.

Abstract: GENETICALLY hypertensive rats appear to be less responsive to noxious stimuli than their normotensive controls. 1 A similar finding has been reported in rats with renal hypertension 1 ' 2 and in humans with essential hypertension.3 Therefore a relationship between the central regulatory mechanisms involved in pain sensitivity and blood pressure may exist.Other data also indicate a possible relationship between these regulatory mechanisms. The hypotensive drug clonidine appears to cause analgesia in rats 4 ' 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1
2

Year Published

1988
1988
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(38 citation statements)
references
References 16 publications
1
34
1
2
Order By: Relevance
“…For example, spontaneously hypertensive rats (SHRs), which have been selectively bred to develop hypertension, demonstrate reduced responsiveness to nociceptive stimuli as early as the third week of life [43,48].…”
Section: Discussionmentioning
confidence: 99%
“…For example, spontaneously hypertensive rats (SHRs), which have been selectively bred to develop hypertension, demonstrate reduced responsiveness to nociceptive stimuli as early as the third week of life [43,48].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, pressor-mediated increases in baroreflex stimulation are frequently offered as a mechanism of hypertensive hypoalgesia~Dworkin, 1988;Ghione, 1996;Maixner, 1991!. Endogenous opioids have also been implicated in this effect, as a number of laboratory animal studies have shown that hypertensive hypoalgesia is reversed by administration of opiate antagonists~Delbarre, Casset-Senon, Delbarre, Sestillange, & Christin, 1982;Saavedra, 1981;Sitsen & de Jong, 1983Wendel & Bennett, 1981!. Other authors have suggested that the arrow of causation is reversed such that, in some cases, hypertension is a consequence of hypoalgesia. As early as 1979, Dworkin and colleagues proposed that blood pressure increases are negatively reinforced by baroreflexmediated dampening of central nervous system responses to aversive events~Dworkin, Filewich, Miller, Craigmyle, & Pickering, 1979!.…”
Section: Theoretical Implications Of Hypertensive Hypoalgesiamentioning
confidence: 99%
“…Consistent with this model, some of the earliest laboratory animal studies of the relationship between hypertension and hypoalgesia indicated that decreased pain perception is not dependent upon high blood pressure. For example, SHR exhibit elevated nociceptive thresholds as early as 4 weeks of age, when their blood pressure levels are not yet significantly different from age-matched controls~Maixner et al., 1982;Sitsen & de Jong, 1983;Wendel & Bennett, 1981!. Further, acute administration of the opiate antagonist naloxone can reverse hypoalgesia in SHR without affecting resting blood pressure~Maix-ner et al, 1982!.…”
Section: Theoretical Implications Of Hypertensive Hypoalgesiamentioning
confidence: 99%
“…27 Hypertension-related hypalgesia has been reported in animal and human studies. [28][29][30] Zamir and Shuber 31 showed that there is a significant positive correlation between BP and pain threshold, determined using a pulp tester, which applies a 600 Hz, 0.1 ms monophasic pulse to the tooth pulp, in healthy normotensive and hypertensive volunteers. Falcone et al 32 also demonstrated that the mean dental pain threshold determined by pulp stimulation significantly correlates with mean DBP in hypertensive patients with coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%